2006
DOI: 10.1177/147323000603400605
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Immune Effects of Dexamethasone in Unilateral Total Knee Replacement

Abstract: The effect of acute pre-surgery dexamethasone treatment on the inflammatory immune and endocrine responses to orthopaedic surgery was investigated. Whole blood samples were obtained before and 5 days after surgery for immune analysis, and serum was obtained before and 6 h, 3 days and 5 days after surgery for endocrine assessment. Dexamethasone did not affect the post-surgery granulocyte response, but inhibited the increase in monocyte count (an average increase of 38.5% was seen in the control group). Peak C-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 21 publications
(15 reference statements)
3
32
1
Order By: Relevance
“…They have been used extensively to reduce the stress response following surgery [10]. A single preoperative dose of glucocorticoid limits complement activation and the acute phase response subsequent to hip and knee arthroplasty [5,23]. Patients who were given dexamethasone (16 mg) prior to undergoing knee arthroplasty reportedly had a 50% decrease in peak CRP concentration on the third postoperative day [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been used extensively to reduce the stress response following surgery [10]. A single preoperative dose of glucocorticoid limits complement activation and the acute phase response subsequent to hip and knee arthroplasty [5,23]. Patients who were given dexamethasone (16 mg) prior to undergoing knee arthroplasty reportedly had a 50% decrease in peak CRP concentration on the third postoperative day [23].…”
Section: Discussionmentioning
confidence: 99%
“…The antiinflammatory effects of glucocorticoids in the postoperative period are well known [5,10,23]. A small single dose of dexamethasone reduces C-reactive protein (CRP) levels by 50% three days following total knee replacement [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past decade, the number of TKAs performed has increased substantially, and future demand is projected to rise rapidly [26,31,35]. However, as a TKA involves extensive bone resection and soft tissue manipulation, patients can experience severe pain during the early postoperative period [13,42,[47][48][49]. Furthermore, many patients experience postoperative nausea and vomiting (PONV) after TKA, owing to not only anesthesia and surgery but also the various agents used for pain control [8,10,20,27].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that perioperative use of single, lowdose corticosteroids significantly decreased inflammatory markers after TKA [23,24,49]. However, despite the potential benefits and reported efficacy in numerous surgical procedures, only a few small studies involving less than 25 patients per group evaluated the efficacy and safety of corticosteroids after TKA [15,24,38,40].…”
Section: Introductionmentioning
confidence: 99%